E-123 In vitro remote aspiration embolectomy for the treatment of acute ischemic stroke. (22nd July 2018) - Rizvi, A; Fitzgerald, S; Daescu, D Dragomir; Kadirvel, R; Castilla, L Rangel; Brinjikji, W; Kallmes, D
Abstract : Background and purpose: 'Remote aspiration', using suction from the proximal internal carotid artery (ICA) to open terminus occlusions, has been reported in small, previous case series. It remains unclear, however, whether remote aspiration for middle cerebral artery (MCA) occlusions in the setting of potential inflow from communicating arteries is feasible. We performed an in vitro study to assess whether suction applied at various locations proximal to an occlusion could successfully aspirate the clot. Methods: A glass model of 4 mm internal diameter (ID) with a 1 mm distal narrowing and a 2 mm side branch to simulate a communicating artery was constructed. A proximal side branch was placed to simulate inflow from the proximal ICA (figure 1). Experimental clot analogues with different histologic proportions of red blood cells (RBCs) and fibrin were created, including RBC-rich, fibrin-rich and mixed clots, and placed under 90 mm Hg mean arterial pressure to lodge at the site of the constriction. The impact of three different sized catheters (ID: 0.088', 0.070', and 0.056') was tested with the tip of the catheter placed remotely either distal or proximal to the collateral branch. Aspiration was attempted with 1) both valves open, to simulate no proximal flow arrest and open collateral; 2) collateral valve open but the proximal valve closed to simulate proximal flow arrest; and 3) both valves closed. The outcome was success or failure of remote aspiration embolectomy. All scenarios were performed in triplicate. Results: For the 0.088' ID catheter, remote aspiration was successful in all conditions. For the 0.070' ID catheter, remote aspiration was unsuccessful without proximal flow arrest, but was successful in all other scenarios. For the 0.056' ID catheter, remote aspiration was successful only with both valves closed. Clot type and catheter tip location had no impact on outcome (figure 2). Conclusions: These experiments suggest that, in a non-collapsible system, remote aspiration embolectomy can be successfully achieved even in the setting of prominent branch arteries, using relatively large aspiration catheters. Proximal flow arrest may facilitate successful remote aspiration for some catheter sizes. Disclosures: A. Rizvi: None. S. Fitzgerald: None. D. Dragomir Daescu: None. R. Kadirvel: None. L. Rangel Castilla: None. W. Brinjikji: None. D. Kallmes: None.